Effect of dietary fat on lipid accumulation and macrophage activation in vivo - Benslimane, Fatiha (2016)
The rat was used as a model for the assessment of a high fat diet (HFD) and HFD/streptozotocin (STZ) induced Type II diabetes upon lipid deposition and development of inflammation in metabolically active tissues.